(untitled) (SAARC Journal of Agriculture, 2019)
Rice (Oryza sativa L.) production technology adoption requires effective farmers’ training for narrowing knowledge gap. This paper assesses the result of community training on the extent of adoption of improved rice production practices in low land rice of south western Bangladesh. A total of 531 farmers were trained through community training approach and 177 farmers were randomly selected for data collection. The extent of adoption of improved rice production practices and reasons for nonadopting technologies were solicited by personal interview with the help of a semi-structured questionnaire. Collected data were analysed using descriptive and inferential techniques. The community training was suited to adopt rice production technologies. The adoption of different rice production technologies was greater by the adopters of Satkhira district compared to Khulna that resulted in significant rice yield difference. The constraints against the adoption of the selected rice production technologies show that a portion of adopters was not convinced to adopt row transplanting, skipped row planting and birds perch for controlling insects, use of appropriate K and S fertilizers due to requirement of higher labour and fertilizer and risk of reduction of rice yield. The integration of other extension methods such as method and result demonstration might enhance the rate of adoption of those rice production technologies. SAARC J. Agri., 17(1): 1-11 (2019)